Analysis of the effective stakeholders' involvement in the development of National Forest Programmes in Europe. (1st March 2016) - Balest, J.; Hrib, M.; Dobšinská, Z.; Paletto, A.
National Forest Programmes represent a wide range of approaches to the process of planning, programming and implementing forest activities in a country. National Forest Programmes are regulated by international rules that highlight the importance of public participation aimed at developing cooperation among stakeholders and at improving the sustainability of forest management. A semi-structured questionnaire was administered by email to 30 national experts involved in the COST Action FP1207. The participatory process was analysed through some key elements: level of participation, structure, strengths and weaknesses of the participatory process. The results show that the most common level of participation is cooperation in all phases of the participatory process and that, overall, the strengths (e.g. review of problems and policies, cross sector approach) outweigh the weaknesses (e.g. time and efforts consuming, lack of trust). The results of the questionnaire bring out some key elements which are useful to analyse the decision making process. Les Programmes Forestiers Nationaux représentent un large éventail d'approches du processus de planification, de programmation et de mise en œuvre des activités forestières dans un pays. Les Programmes Forestiers Nationaux sont régis par des règles internationales qui mettent en évidence l'importance de la participation du public. Celle-ci vise à développer la coopération entre les parties prenantes et à améliorer la gestion durable des forêts. Un questionnaire semi-structuré a été envoyé par email à 30 experts nationaux impliqués dans la COST Action FP1207. Le processus participatif a été analysé selon certains éléments clés: niveau de participation, structure du processus, forces et faiblesses du processus participatif. Les résultats montrent que le niveau de participation le plus commun est la coopération dans toutes les phases du processus participatif. En outre, les points forts (examen des problèmes et des politiques, approche intersectorielle) l'emportent sur les faiblesses (coûteux en temps et effort, manque de confiance). Les résultats apportent quelques éléments clés qui sont utiles pour analyser le processus de prise de décision.Los Programas Forestales Nacionales representan una amplia gama de enfoques al proceso de planificación, programación y ejecución de actividades forestales en un país. Los Programas Forestales Nacionales están regulados por normas internacionales que ponen de relieve la importancia de la participación pública dirigida a desarrollar cooperación entre las partes interesadas y a mejorar la gestión forestal sostenible. Un cuestionario semiestructurado se envió por correo electrónico a 30 expertos nacionales involucrados en la COST Action FP1207. El proceso participativo se analizó utilizando algunos elementos clave: nivel de participación, estructura, fortalezas y debilidades del proceso participativo. Los resultados muestran que la cooperación es el nivel más común de participación en todas las fases del proceso participativo. Además las fortalezas (revisión de problemas y politicas, enfoque intersectorial) superan las debilidades (consumo de tiempo y esfuerzo, falta de confianza). Los resultados del cuestionario ponen en evidencia algunos elementos clave que son útiles para analizar el proceso de toma de decisiones.